Role of macrophages in pulmonary arterial hypertension - Zhang, Meng-Qi; Wang, Chen-Chen; Pang, Xiao-Bin; Shi, Jun-Zhuo; Li, Hao-Ran; Xie, Xin-Mei; Wang, Zhe; Zhang, Hong-Da; Zhou, Yun-Feng; Chen, Ji-Wang; Han, Zhi-Yan; Zhao, Lu-Ling; et al. (Frontiers in Immunology, 2023)
Pulmonary arterial hypertension (PAH) is a severe cardiopulmonary vascular disease characterized by progressive pulmonary artery pressure elevation, increased pulmonary vascular resistance and ultimately right heart failure. Studies have demonstrated the involvement of multiple immune cells in the development of PAH in patients with PAH and in experimental PAH. Among them, macrophages, as the predominant inflammatory cells infiltrating around PAH lesions, play a crucial role in exacerbating pulmonary vascular remodeling in PAH. Macrophages are generally polarized into (classic) M1 and (alternative) M2 phenotypes, they accelerate the process of PAH by secreting various chemokines and growth factors (CX3CR1, PDGF). In this review we summarize the mechanisms of immune cell action in PAH, as well as the key factors that regulate the polarization of macrophages in different directions and their functional changes after polarization. We also summarize the effects of different microenvironments on macrophages in PAH. The insight into the interactions between macrophages and other cells, chemokines and growth factors may provide important clues for the development of new, safe and effective immune-targeted therapies for PAH.